2002
DOI: 10.1034/j.1600-0714.2002.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic tumors in Chile: a study of 362 cases

Abstract: Odontogenic tumors are uncommon lesions in the Chilean population and malignant odontogenic tumors are very rare. The relative frequency of various types of odontogenic tumors, as well as the age and gender distribution are similar to those reported in the North American series and different from those found in recently published Asian and African series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

51
119
12
17

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(242 citation statements)
references
References 16 publications
51
119
12
17
Order By: Relevance
“…13 Lesions such as the squamous odontogenic tumor and the ameloblastic fibrodontoma were found in a single case each; both were females and presented mandibular pain. Our study confirmed the low frequency of these neoplasms as shown in other studies, 3,7,12,14 which underlines their rarity.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…13 Lesions such as the squamous odontogenic tumor and the ameloblastic fibrodontoma were found in a single case each; both were females and presented mandibular pain. Our study confirmed the low frequency of these neoplasms as shown in other studies, 3,7,12,14 which underlines their rarity.…”
Section: Discussionsupporting
confidence: 80%
“…5,6,10 This was the most common of these tumors in the Americas, as reported by Ochsenius et al, 14 MosquedaTaylor et al, l3 and Daley et al; 10 odontomas are least frequent in Africans 6 and Chinese. 7 There were 54 cases of odontomas in our 15-year study (22.1%) ( Table 2).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…These findings are similar to the ones reported by Luo and Li (16), da-Costa et al (18) and Johnson et al (22). The mandible was 2.5 times more common than the maxilla which is similar to previous studies (8,18,21,22). KCOT was the most prevalent OT in this study, followed by AMB and ODO.…”
Section: Discussionsupporting
confidence: 82%
“…This low frequency of malignant tumors is similar to those reported in others countries (7)(8)(9)(10)(11)(12)19), but it is different than those reported in China that present more than 5% of cases as malignant tumors (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). We have observed a greater incidence of OTs in the female gender, result also found by Gaitán-Cepeda et al (30).…”
Section: Discussionsupporting
confidence: 55%